Efficacy and safety of combined low‐dose rituximab regimen for chronic inflammatory demyelinating polyradiculoneuropathy - Ying Du; Qi Yan; Chuan Li; Wenping Zhu; Chao Zhao; Yunfeng Hao; Lin Li; Dan Yao; Xuan Zhou; Ying Li; Yuting Dang; Rong Zhang; et al. (Annals of Clinical and Translational Neurology)
Abstract Objective To determine the efficacy and safety of combined low‐dose rituximab with conventional therapy for chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) treatment. Methods Total 73 patients with CIDP were enrolled for the retrospective cohort study, and divided into conventional first‐line therapy cohort (n = 40) and combined low‐dose rituximab (100 mg per infusion) cohort (n = 33). The outcome measures include scores of I‐RODS, mRS, INCAT, ONLS, TSS, and COMPASS 31 scale at baseline and regular four visits (4, 16, 28, and 52 weeks), as well as proportion of favorable response and outcome, corticosteroids dosage, and deterioration occurrence during follow‐up. Results Compared to conventional therapy cohort, combined rituximab cohort presented better improvements and higher proportion of favorable response in scales assessments at each visit, as well as significantly reduced corticosteroids dosage and deterioration occurrence during the follow‐up. Analyses of subgroups showed better improvements in both typical CIDP and CIDP variants in combined rituximab cohort than those in conventional therapy cohort, but had no differences between each other. Early initiating combined rituximab regimen (<10 weeks) showed better improvements than delayed initiation (≥10 weeks) at the first three visits within 28 weeks, while had no difference in favorable prognoses at the last visit of 52 weeks after once reinfusion. No rituximab correlated serious adverse events were reported in our patients. Interpretation Our simplified regimen of combined low‐dose rituximab has been firstly demonstrated for the better efficacy and safety than conventional therapy in CIDP treatment.